(untitled) (The Pakistan Development Review, 1982)
In the Spring 1981 edition of this Review, A.R. Kemal presented evidence on ’substitution elasticities’, estimated over the period 1960-70, in sixteen two-digit manufacturing industries in Pakistan [8]. After applying several variants of the basic ’production function’ approach, the author argued that the elasticities of substitution in Pakistan were generally low and/or insignificant and therefore a manifestation of Pakistan’s ’technological dependence’; that these results are ’consistent’ with similar estimates for other developing countries; and that because of the low value of the elasticities, the removal of factor price distortions, while necessary to the attainment of a more labour-intensive pattern of development, needs to be supported by policies aimed al subsidizing the developing of indigenous technologies.